Stroke survivors' experiences of upper limb recovery: a systematic review of qualitative studies. (28th October 2020) - Meads, Hayley; Hunt, Jamie; Page, Alister; Withy, Lee; Plowman, Rose; Calder, Allyson
Abstract: Background: Many stroke survivors do not regain full function of their upper limb, which can have a devastating effect for participation in daily activities. Objectives: This research aimed to systematically review stroke survivors' lived experiences of upper limb recovery. Our objectives explored stroke survivors' barriers and facilitators to recovery and the clinical implications for health professionals. Methods: We searched the databases of MEDLINE, EMCARE, CINAHL, Scopus, and Web of Science using keywords and synonyms of 'stroke survivors', 'upper limb', 'recovery', and 'perspectives'. Studies were appraised using the Critical Appraisal Skills Programme (CASP) Qualitative checklist. Data were analyzed descriptively and analytically using a thematic synthesis approach. We graded the emerging descriptive themes using the Confidence in the Evidence from Reviews of Qualitative Research (GRADE-CERQual). A protocol was registered apriori in PROSPERO (ID:181379). Results: Eleven studies were included for review. Nine descriptive themes and three analytical themes emerged from the data that influenced upper limb recovery: 1) psychological wellbeing, 2) rehabilitation, and 3) relationships. Conclusions: Barriers to upper limb recovery included health professionals' attitudes particularly towards a lack of inclusivity in goal setting. In addition, stroke survivors perceived therapists focused on upper limb compensation rather than functional recovery, which was disempowering. Facilitators that enhanced recovery included the stroke survivors' personal attitudes (psychological well-being) and external supports from family, friends, health professionals, and stroke survivor peers. Such supports enhanced the stroke survivors' journey towards acceptance and adapting to their 'new normal' thus building confidence and self-efficacy to re-establish identity.